Next Generation CD40 Agonistic Antibodies for Cancer Immunotherapy - Salomon, Ran; Dahan, Rony (Frontiers in Immunology, 2022)
The clinical use of anti-CD40 agonist monoclonal antibodies (mAbs) is aimed at recruiting the immune system to fight the tumor cells. This approach has been demonstrated to be effective in various preclinical models. However, human CD40 Abs displayed only modest antitumor activity in cancer patients, characterized by low efficacy and dose-limiting toxicity. While recent studies highlight the importance of engineering the Fc region of human CD40 mAbs to optimize their agonistic potency, toxicity remains the main limiting factor, restricting clinical application to suboptimal doses. Here, we discuss the current challenges in realizing the full potential of CD40 mAbs in clinical practice, and describe novel approaches designed to circumvent the systemic toxicity associated with CD40 agonism.